High-resolution speckle imaging - Howell, Steve B.; Horch, Elliott P. (Physics Today, 2018)
3 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Wide-field speckle techniques for small, urban telescopes - Granucci, Nicole M.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
Recent work with the NESSI speckle camera at Kitt Peak and the 'Alopeke speckle camera at Gemini-North indicates that speckle data reduction techniques can be successfully modified to produce high-resolution images over fields that are at least tens of arc seconds across. While these wide-field speckle image reconstructions are not diffraction-limited, the improvement in resolution over the seeing-limited case can be substantial. In this paper, we explore the application of these techniques to data taken with a small (0.6-m) telescope in an urban environment. Many telescopes located in urban communities, such as New Haven, Connecticut, where Southern Connecticut State University resides, have limited use scientifically due to substantial light pollution, poor seeing, poor telescope tracking, and other issues. We will present initial data using our set-up and discuss the potential for this approach for improving the imaging capabilities of small telescopes on our campus and beyond.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-406-183-484-56X, pop00246
Keywords: Cameras; Diffraction limited; High resolution image; Image enhancement; Image reconstruction; Imaging capabilities; Interferometry; Pollution; Reduction techniques; Shift-and-add; Speckle; Speckle imaging; Telescopes; Unsharp masking; Urban environments; dept.phy; shift-and-add techniques; unsharp masking

Stellar photon correlation detection with the Southern Connecticut stellar interferometer - Weiss, Samuel A.; Rupert, Justin D.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a portable optical intensity interferometer located on the campus of Southern Connecticut State University in New Haven, Connecticut. Since its completion in 2016, the instrument has been used to take engineering data of bright stars. This paper will discuss the data collection and analysis methods, as well as the progress toward reliably measuring a significant stellar photon correlation. Vega has been the main star chosen for test observations to date because its diameter is well known by other methods, and it is not an extended source for the baselines used. The correlation peak in the processed data is compared to theoretical expectations. Given our expected sensitivity, a significant correlation peak is expected for small baselines (~2 m) to appear after a few hours of observation. So far, the observations indicate that the correlation peak is at the expected time delay, and the signal-to-noise ratio roughly scales as predicted.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-933-668-471-503, pop00212
Keywords: Avalanche diodes; Correlation peaks; Engineering data; Extended sources; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Optical intensities; Particle beams; Photon correlation; Photons; Quantum optics; Signal to noise ratio; Single photon avalanche diode; Stars; Stellar interferometers; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

The Three-dimensional orbit, orbital parallax, and individual masses of the double-lined spectroscopic binaries HD 183255, HD 114882, and HD 30712 - Docobo, J. A.; Campo, P. P; Gomez, J.; Horch, Elliott P. (The Astronomical Journal, 2018)
Recent speckle observations performed at the Discovery Channel Telescope, the Gemini North Telescope, and the Special Astrophysical Observatory 6 m Telescope have permitted us to calculate the visual orbit of SB2 HD 114882 for the first time and to improve the visual orbits of two other SB2 systems, HD 30712 and HD 183255, using algorithms published by the authors of this research. Recently, new high-quality spectroscopic orbits have been obtained for these binaries by other authors. We determine their 3D orbits, individual masses, and orbital parallaxes, and present them in this paper. The parallaxes are compared with those available from the Gaia mission, and a comparison between the values confirms the precision of the results obtained here. © 2018. The American Astronomical Society. All rights reserved.
4 citations (Crossref) [2023-10-31]
Keywords: astrometry; binaries: spectroscopic; binaries: visual; dept.phy; peer-reviewed; stars: fundamental parameters; techniques: interferometric

Stellar companions of exoplanet host stars in K2 - Matson, Rachel A.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (The Astronomical Journal, 2018)
It is well established that roughly half of all nearby solar-type stars have at least one companion. Stellar companions can have significant implications for the detection and characterization of exoplanets, including triggering false positives and masking the true radii of planets. Determining the fraction of exoplanet host stars that are also binaries allows us to better determine planetary characteristics as well as establish the relationship between binarity and planet formation. Using high angular resolution speckle imaging, we detect stellar companions within ∼1 arcsec of K2 planet-candidate host stars. Comparing our detected companion rate to TRILEGAL star count simulations and known detection limits of speckle imaging, we estimate the binary fraction of K2 planet host stars to be 40%-50%, similar to that of Kepler exoplanet hosts and field stars. © 2018. The American Astronomical Society. All rights reserved.
70 citations (Crossref) [2023-10-31]
Keywords: binaries: general; binaries: visual; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

The NN-explore exoplanet stellar speckle imager: Instrument description and preliminary results - Scott, Nicholas J.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (Publications of the Astronomical Society of the Pacific, 2018)
A new speckle and wide-field imaging instrument for the WIYN telescope called NN-EXPLORE Exoplanet Stellar Speckle Imager (NESSI) is described. NESSI offers simultaneous two-color diffraction-limited imaging and wide-field traditional imaging for validation and characterization of transit and precision RV exoplanet studies. Many exoplanet targets will come from the NASA K2 and Transiting Exoplanet Survey Satellite (TESS) missions. NESSI is capable of resolving close binaries at sub-arcsecond separations down to the diffraction limit and >6 mag contrast difference in the visible band on targets as faint as 14th mag. Preliminary results from the instrument commissioning at WIYN and demonstrations of the instrument’s capabilities are presented. © 2018. The Astronomical Society of the Pacific. Printed in the U.S.A.
68 citations (Crossref) [2023-10-31]
Keywords: Binaries (including multiple): close; Instrumentation: high angular resolution; Instrumentation: interferometers; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Speckle interferometry at SOAR in 2016 and 2017 - Tokovinin, Andrei; Mason, Brian D.; Hartkopf, William I.; Mendez, Rene A.; Horch, Elliott P. (The Astronomical Journal, 2018)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2016 and 2017 are given, totaling 2483 measurements of 1570 resolved pairs and 609 non-resolutions. We describe briefly recent changes in the instrument and observing method and quantify the accuracy of the pixel scale and position angle calibration. Comments are given on 44 pairs resolved here for the first time. The orbital motion of the newly resolved subsystem BU 83 Aa,Ab roughly agrees with its 36-year astrometric orbit proposed by J. Dommanget. Most Tycho binaries examined here turned out to be spurious. © 2018. The American Astronomical Society. All rights reserved..
30 citations (Crossref) [2023-10-31]
Keywords: binaries: visual; dept.phy; peer-reviewed

Prospects for wireless optical intensity interferometry with the Southern Connecticut stellar interferometer - Horch, Elliott P.; Weiss, Samuel A.; Rupert, Justin D.; LaRue, Ryan; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a two-telescope astronomical intensity interferometer that was completed in June 2016 and has been taking photon correlation data since that time. It uses single-photon avalanche diode (SPAD) detectors at the telescope focal plane and a central timing module, which records the signals from both telescopes simultaneously. In the observations taken to date, single-pixel SPADs have been connected to signal cables that stretch from each telescope to the timing module. However, we are now in the process of making the instrument “wireless” by using a separate timing module at each telescope and synchronizing the signals recorded using GPS timing cards. We have also upgraded one of the two stations with an 8-pixel SPAD device, which allows us to achieve higher count rates in a variety of observing conditions. In this paper, we report on the current state of the instrument, including engineering tests made in preparation for wireless operation, and we discuss the expected capabilities in that mode.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-838-080-681-906, pop00166 tex.type: [object Object]
Keywords: Avalanche diodes; Engineering tests; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Particle beams; Photon correlation; Photons; Single photon avalanche diode; Stars; Stellar interferometers; Telescopes; Timing module; Wireless operation; Wireless-optical; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Zodiacal Exoplanets in Time (ZEIT). VII. A temperate candidate Super-Earth in the Hyades Cluster - Vanderburg, Andrew; Mann, Andrew W.; Rizzuto, Aaron; Bieryla, Allyson; Kraus, Adam L.; Berlind, Perry; Calkins, Michael L.; Curtis, Jason L.; Douglas, Stephanie T.; Esquerdo, Gilbert A.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2018)
Transiting exoplanets in young open clusters present opportunities to study how exoplanets evolve over their lifetimes. Recently, significant progress detecting transiting planets in young open clusters has been made with the K2 mission, but so far all of these transiting cluster planets orbit close to their host stars, so planet evolution can only be studied in a high-irradiation regime. Here, we report the discovery of a long-period planet candidate, called HD 283869 b, orbiting a member of the Hyades cluster. Using data from the K2 mission, we detected a single transit of a super-Earth-sized (1.96 0.12 R ⊕) planet candidate orbiting the K-dwarf HD 283869 with a period longer than 72 days. As we only detected a single-transit event, we cannot validate HD 283869 b with high confidence, but our analysis of the K2 images, archival data, and follow-up observations suggests that the source of the event is indeed a transiting planet. We estimated the candidate's orbital parameters and find that if real, it has a period P ≈ 100 days and receives approximately Earth-like incident flux, giving the candidate a 71% chance of falling within the circumstellar habitable zone. If confirmed, HD 283869 b would have the longest orbital period, lowest incident flux, and brightest host star of any known transiting planet in an open cluster, making it uniquely important to future studies of how stellar irradiation affects planetary evolution. © 2018. The American Astronomical Society. All rights reserved..
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-063-848-375-694, pop00021 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: detection; stars: individual (HD 283869)

275 candidates and 149 validated planets orbiting bright stars in K 2 campaigns 0–10 - Mayo, Andrew W.; Vanderburg, Andrew; Latham, David W.; Bieryla, Allyson; Morton, Timothy D.; Buchhave, Lars A.; Dressing, Courtney D.; Beichman, Charles; Berlind, Perry; Calkins, Michael L.; Ciardi, David R.; Crossfield, Ian J. M.; et al. (The Astronomical Journal, 2018)
Since 2014, NASA's K2 mission has observed large portions of the ecliptic plane in search of transiting planets and has detected hundreds of planet candidates. With observations planned until at least early 2018, K2 will continue to identify more planet candidates. We present here 275 planet candidates observed during Campaigns 0-10 of the K2 mission that are orbiting stars brighter than 13 mag (in Kepler band) and for which we have obtained high-resolution spectra (R = 44,000). These candidates are analyzed using the vespa package in order to calculate their false-positive probabilities (FPP). We find that 149 candidates are validated with an FPP lower than 0.1%, 39 of which were previously only candidates and 56 of which were previously undetected. The processes of data reduction, candidate identification, and statistical validation are described, and the demographics of the candidates and newly validated planets are explored. We show tentative evidence of a gap in the planet radius distribution of our candidate sample. Comparing our sample to the Kepler candidate sample investigated by Fulton et al., we conclude that more planets are required to quantitatively confirm the gap with K2 candidates or validated planets. This work, in addition to increasing the population of validated K2 planets by nearly 50% and providing new targets for follow-up observations, will also serve as a framework for validating candidates from upcoming K2 campaigns and the Transiting Exoplanet Survey Satellite, expected to launch in 2018. © 2018. The American Astronomical Society. All rights reserved.
114 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-080-708-221-69X, pop00001, pop00002 tex.type: [object Object]
Keywords: dept.phy; methods: data analysis; peer-reviewed; planets and satellites: detection; techniques: photometric